Earth's CO2 battle: a view from space. Issue 1 (10th February 2023) - Cressie, Noel; Zammit-Mangion, Andrew; Jacobson, Josh; Bertolacci, Michael
Abstract: Our environment is undergoing rapid change as greenhouse gases warm the planet. Noel Cressie, Andrew Zammit-Mangion, Josh Jacobson, and Michael Bertolacci use WOMBAT, a Bayesian hierarchical statistical framework, to infer the spatio-temporal distribution of CO2 surface fluxes Abstract : Our environment is undergoing rapid change as greenhouse gases warm the planet. Noel Cressie, Andrew Zammit-Mangion, Josh Jacobson, and Michael Bertolacci use WOMBAT, a Bayesian hierarchical statistical framework, to infer the spatio-temporal distribution of CO2 surface fluxes